Evidence that molecules in molecular junctions may not be subject to the entire external perturbation applied to electrodes - Bâldea, Ioan (Langmuir, 2020)
Whether molecules forming molecular junctions are really subject to the entire external perturbation applied to electrodes is an important issue, but so far, it has not received adequate consideration in the literature. In this paper, we demonstrate that, out of the temperature difference ΔTelectr between electrodes applied in thermopower measurements, molecules only feel a significantly smaller temperature difference (ΔTmolec < ΔTelectr). Rephrasing, temperature drops at metal-molecule interfaces are substantial. Our theoretical analysis to address this problem of fundamental importance for surface science is based on experimental data collected via ultraviolet photoelectron spectroscopy, transition voltage spectroscopy, and Seebeck coefficient measurements. An important practical consequence of the presently reported finding is that the energetic alignment of the frontier molecular orbital (HOMO or LUMO) of the embedded molecules with respect to the metallic Fermi level position deduced from thermopower data—and this is frequently the case in current studies of molecular electronics—is substantially overestimated. Another important result presented here is that, unlike the exponential length dependence characterizing electric conduction (which is a fingerprint for quantum tunneling), thermal conduction through the molecules considered (oligophenylene thiols and alkane thiols) exhibits a length dependence compatible with classical physics.
Gesehen am 11.03.2020